The debt-growth nexus in poor countries: a reassessment - Andrea F. Presbitero (Kiel Institute for the World Economy (IfW), 2007)
This paper investigates the relationship between external indebtedness and economic growth, with a particular attention to LICs, for which the theoretical arguments of debt overhang and liquidity constraint have to be reconsidered. The estimation of a growth model, with a panel of 121 developing countries, supports a negative and linear relationship between past values of the NPV of external public debt and current economic growth. This could be due to the ?extended debt overhang?, according to which a large indebtedness leads to misallocation of capital and discourage long-term investment and structural reforms.
Keywords: O11; F34; C33; H63; 330; External Debt; HIPC; Debt Relief; Economic Growth